CO2 capture, separation, and storage on MgSiP2 monolayer: A first-principles study. (January 2023) - Yu, Jiahui; He, Chaozheng; Huo, Jinrong; Zhao, Chenxu; Yu, Lingmin
Abstract: New materials that can effectively capture, separate, and store CO2 play a key role in suppressing the CO2 concentration in the atmosphere and alleviating the greenhouse effect. Herein, we report a study of the adsorption of gaseous CO2, N2, CH4, and H2 on a 2D MgSiP2 monolayer. The results demonstrate that MgSiP2 monolayer is able to selectively capture CO2 from CO2 /H2 gas mixture. However, CO2 cannot be effectively captured from a mixture of CO2, N2, and CH4 . Further research shows that the MgSiP2 monolayer can capture up to eight CO2 molecules with a maximum capture capacity of 20.42 wt%, indicating its good CO2 storage capacity. Moreover, compared with other studies, the 2D MgSiP2 surface that is not modified can release CO2 at relatively high temperatures. This work focuses on providing important information about a multifunctional 2D material, which is an indispensable support for the practical application of the 2D MgSiP2 structure. Highlights: 2D MgSiP2 is able to capture and separate CO2 from CO2 /H2 gas mixture. 2D MgSiP2 can store CO2 stably with a maximum capture capacity of 20.42 wt%. Pristine MgSiP2 monolayer can release CO2 at a relatively high temperature.